THE PERCEPTION OF STUDENTS TOWARD TEACHER VOICE TONE IN CLASSROOM INTERACTION : A LITERATURE REVIEW - Nurchintyawati, Insani (Journal of Language, Literature and Teaching, 2023)
Communication is the process of how communicators convey information or a message to his/her communicant, to create a common meaning with each other. Communication consists of verbal communication and non-verbal communication. However, research shows that 80% of human communication is done non-verbally conveyed. Non-verbal communication is very important because it can strengthen, clarify and complement the verbal communication. One of non-verbal communication is mostly done is voice of tone or paralanguage. Voice of tone is basic tool in human communication. It can have a huge impact on teaching and relationships between teacher and students. In the process of learning in the classroom teachers voice tones can lead to a variety of student perceptions. This is quite interesting for in further study. Therefore, this paper will be explained about students’ perception toward teacher voice tone in classroom interaction.Keywords: Communication, nonverbal communication, teacher voice tone, students’ perception, classroom interaction.